POLA MAKAN ANAK DENGAN STATUS GIZI ANAK USIA 6-8 TAHUN DI SD WILAYAH KELURAHAN CEMPAKA - Rahmayanti, Devi; Damayanti, Emmelia Astika F. (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
Factor nutritional adequacy in children, is determined by the adequacy of food consumption,whereas in the past tended to be more active children to choose their own food that he liked.Patterns of food consumption in elementary school children, especially in urban areasexperienced a change from the traditional diet to a western diet which is generally an unhealthydiet because it has a low nutrient content but high in calories and fat. The purpose of this studywas to analyze the relationship between the child's diet and nutritional status of children aged 6-8years in elementary school Cempaka village area. This type of research is non-experimentalstudies using cross sectional study design with a purposive sampling techniques. Total sample of30 mothers and 30 children. The research instrument used was a questionnaire filled diet ofchildren whose mothers and weight scales and measuring height. Data were analyzed using theSpearman rank test. Results vast majority of children have diets were as many as 24 children(80%) with good nutritional status of10 children (33.3%) and nutritional status over a total of 14children (46.7%). Children with good diets as much as 6 children (20%) had good nutritionalstatus. There is a relationship between the child's diet and nutritional status of children aged 6-8years and there is a child's diet and nutritional status of children aged 6-8 years in rural areasCempaka SD.